INDUSTRIALISASI PEDESAAN DAN PEMBERDAYAAN EKONOMI PETANI DESA SITIMULYO, PIYUNGAN, BANTUL, YOGYAKARTA - Sulistyaningsih Sulistyaningsih (Jurnal Sosiologi Reflektif, 2013)
Existence of industrialization for Indonesia, as one of the developing countries is the strategy of choice in the model development focused one conomic growth. Industrialization selection model policyh as an impact on the dynamics of industrialization of agriculture in the countryside. One side, it is the growth of the national economy rising sharply, yet on the other hand makes a very striking imbalance, especially in the agricultural sector. Conditions of agricultural industrialization, in this case, the agricultural sector has experienced marginality as a result of state policies that are not in favor of the farmers. As a result, rural industrialization there is no synergy in efforts to empower farmers in the rural economy. These conditions experienced by farmers in the Sitimulyo village Piyungan districts Bantul Yogyakarta. Sitimulyo is one of village at Piyungan sub-distric a part of Bantul regency of Yogyakarta City, which is the area of industrial development. The existence of this policy has any impact either directly or indirectly to the economic empowerment of farmers in the Piyungan District Sitimulyo village. Agricultural landin the village of Sitimulyo coincides with the presence of companies such as PT Perwita Karya, CV. Aneka Darma, PT. Pengolahan Plastik, PT. Adi Satria Abadi, PT. Don Young, Koperasi Umbul Jaya (Relocation of IKM Aluminum) and Kids Fun.The purpose of the study is to know the impact of industrialization on the economic empowerment of rural farmers in the village and to know Sitimulyo empowerment efforts undertaken by the village government and farmer groups that are economically powerless in the midst of the crush ofindustrialization. The theory used in this study is industrialization theory and empowerment. The research method used is a qualitative research method. Methods of data collection are done through observation and in-depth interviews. Data analysis was conducted by reviewing all data from various sources. Having read, studied and analyzed the next step is to conduct data reduction and interpretation of data. The research results are as follows: rural industrialization affects the economic empowerment of farmers in the village Sitimulyo, either directly or indirectly, either positive or negative impact. Positive impact is the local labor absorption. The negative impact is water short ages for most farmers irrigate their field sand the presence of was teand pollution.This condition affects the quantity and quality aspects of plant productivity that affect farmers’ income. Farmers’ income simply to meet subsistence needs. Empowerment efforts is undertaken by the village government and Sidomakmur farmer group in the Sitimulyo village through capacity building (through the field school for farmers in the Sitimulyo village), facilitation of networks (network) and assistance (seeds, agricultural tools).